SiNCED1, a 9-cis-epoxycarotenoid dioxygenase gene in Setaria italica, is involved in drought tolerance and seed germination in transgenic Arabidopsis - Huang, Yuan; Jiao, Yang; Yang, Sha; Mao, Dandan; Wang, Feng; Chen, Liangbi; Liang, Manzhong (Frontiers in Plant Science, 2023)
Foxtail millet (Setaria italica L.) is a vital cereal food crop with promising development and utilization potential because of its outstanding ability to resist drought stress. However, the molecular mechanisms underlying its drought stress resistance remains unclear. In this study, we aimed to elucidate the molecular function of a 9-cis-epoxycarotenoid dioxygenase gene, SiNCED1, in the drought stress response of foxtail millet. Expression pattern analysis showed that SiNCED1 expression was significantly induced by abscisic acid (ABA), osmotic stress, and salt stress. Furthermore, ectopic overexpression of SiNCED1 could enhance drought stress resistance, by elevating endogenous ABA levels and promoting stomatal closure. Transcript analysis indicated that SiNCED1 modulated ABA-related stress responsive gene expression. In addition, we found that ectopic expression of SiNCED1 delayed seed germination under normal and abiotic stress conditions. Taken together, SiNCED1 plays a positive role in drought tolerance and seed dormancy of foxtail millet by modulating ABA biosynthesis. In conclusion, this study has revealed that SiNCED1 is an important candidate gene in the improvement of drought stress tolerance in foxtail millet, and could be beneficial in the breeding and investigation of drought tolerance in other agronomic crops.